2014
DOI: 10.1073/pnas.1402617111
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of growth by proteorhodopsin phototrophy involves regulation of central metabolic pathways in marine planktonic bacteria

Abstract: Proteorhodopsin (PR) is present in half of surface ocean bacterioplankton, where its light-driven proton pumping provides energy to cells. Indeed, PR promotes growth or survival in different bacteria. However, the metabolic pathways mediating the light responses remain unknown. We analyzed growth of the PR-containing Dokdonia sp. MED134 (where light-stimulated growth had been found) in seawater with low concentrations of mixed [yeast extract and peptone (YEP)] or single (alanine, Ala) carbon compounds as model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
131
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(137 citation statements)
references
References 52 publications
3
131
0
Order By: Relevance
“…A similar growth-phase dependence of PR expression was observed in the naturally PRcontaining Dokdonia sp. MED134 (6). The drop in PR content during the stationary phase may be in part due to the promoter we selected, because it is known that psbA2 expression and transcript stability are light-intensity dependent (68)(69)(70)(71)(72)(73), and so is heterologous expression driven by this promoter (74,75).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar growth-phase dependence of PR expression was observed in the naturally PRcontaining Dokdonia sp. MED134 (6). The drop in PR content during the stationary phase may be in part due to the promoter we selected, because it is known that psbA2 expression and transcript stability are light-intensity dependent (68)(69)(70)(71)(72)(73), and so is heterologous expression driven by this promoter (74,75).…”
Section: Discussionmentioning
confidence: 99%
“…The drop in PR content during the stationary phase may be in part due to the promoter we selected, because it is known that psbA2 expression and transcript stability are light-intensity dependent (68)(69)(70)(71)(72)(73), and so is heterologous expression driven by this promoter (74,75). It is worth noting that several of the recently discovered proteorhodopsins in 'chemotrophic', often psychrophilic, bacteria only contribute detectably to growth rate or cell yield when the cells are stressed and/or in stationary phase (6,(14)(15)(16)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dokdonia MED134 was the first bacterium shown to divide faster in the light compared to the dark under low organic carbon concentrations (Gómez-Consarnau et al, 2007). Subsequent studies on the same strain have shown that growth stimulation by PR in the light is linked to changes in central metabolism (Palovaara et al, 2014) and/or transcriptional changes associated with Na + pumping (Kimura et al, 2011). Recently, another flavobacterium, Nonlabens marinus S1-08, containing three different rhodopsin types (H + , Na + and Cl − pumps) has been described.…”
Section: Introductionmentioning
confidence: 99%